CALLOUS-UNEMOTIONAL TRAITS IN ADOLESCENTS - Ali, Fatima Abdul-Jabbar; Jassim, Ahmed Latif (Al-Adab Journal, 2021)
It is intended by unemotional tough traits, lack of guilt, lack of emotional participation, lack of interest in performance and abuse of others in order to achieve some personal gain. The current research aims to identify the following: 1. The level of severe callous-Unemotional traits in adolescents, 2. The level of differences in callous-Unemotional traits Affective according to the gender variable (male / female), and in order to achieve the objectives of the research, the researcher has adopted the measure of severe callous-Unemotional traits prepared and developed by Paul J. Frick Paul J. Frick (2004), and the scale consisted in its final form of (22) paragraphs, after deleting two paragraphs in the procedures for building the scale, which was applied to an analytical sample of (400) adolescents, of (200) males and (200) females, Then the scale was applied to the application sample, which amounted to (200) adolescents, including (90) males and (110) females from middle school students in Baghdad governorate, by applying the electronic form. The research reached the following results: 1. The level of severe features Affective in adolescents does not rise to the level of statistical significance. 2. There are statistically significant differences in the level of callous-Unemotional traits features according to the gender variable (male/ female) and in favor of males, and the researcher came up with recommendations, including: - The need for the Ministry of Education to direct educators and workers in the educational corps to monitor children's behavior in school and cooperate with the family in Focusing on the behavior of their children, which helps in early diagnosis of behavioral problems, including severe, unemotional traits.